Neither height nor depth: discerning the cosmology of Romans - Gaventa, Beverly Roberts (Scottish journal of theology, 2011)
Although the term cosmos in Romans is largely used in a neutral fashion to refer to humanity, as has been demonstrated by Edward Adams, the cosmos is nevertheless the location of a conflict between God and anti-God powers, most prominently the powers of Sin and Death. This conflict comes into view in Paul's repeated use of the language drawn from the arenas of slavery, statecraft and the military (especially in Romans 5–8). In the death and resurrection of Jesus Christ, Sin and Death are themselves defeated (5:12–21; 6:8–11), but they are not yet destroyed. The conflict continues in the present as comes to expression in Romans 8, where Paul claims that the whole of creation (both human and non-human) waits for deliverance. And the conflict continues especially in 8:31–9, with its strong assertions that no power is powerful enough to separate humanity from its rightful Lord, assertions that would be unnecessary apart from the conviction that there are indeed anti-God powers whose goal is to reclaim human lives. Paul's cosmology, then, is less concerned with the order and wonder of the cosmos than with its need of redemption, a redemption begun but not yet complete. Cosmology and soteriology are inextricably connected to one another.